Experiential Marketing Strategy And Its Influence On Brand Identity In The Café Business - Yani, Mia Indri; Maulana, Yogi Sugiarto; Hadiani, Dian (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research Objectives: The purpose of this research is to determine the influence of experiential marketing on brand identity. Design/Method/Approach: The research method used is explanatory research. The sample was 94 people using simple random sampling techniques. Data collection techniques through literature studies and field studies using questionnaires, observation, and documentation. Data analysis techniques are carried out by processing data statistically. Research Findings: Based on the research results, it is known that the implementation of experiential marketing program has not been implemented optimally considering that there are still several indicators that are lacking in implementation, such as Café Overtime not providing a buy one get two promo and the lack of providing complimentary products for every minimum purchase. The creation of the brand identity at Café Overtime is good, but it still needs to be improved regarding how the brand can create a positive impression and increase creativity in developing the café so that sales activities can increase. Based on statistical tests, the experiential marketing program influences brand identity by 71.30%, while the remaining 28.70% is influenced by other factors not researched. Theoretical Contribution/ Originality: This research contributes to research on how to build brand identity, especially in the café industry. Practical Implications: In the café industry, brand identity can be built through experiential marketing programs, especially regarding the spatial layout and atmosphere of cafés with distinctive characteristics. Research Limitations: This research has limitations in the research location only the culinary sector.